Soft tissue sarcomas: Evaluation by immunohistochemistry - Al Obaidi, Ibtisam Hussein (Journal of the Faculty of Medicine Baghdad, 2020)
Soft tissue sarcomas represent a histologically heterogenous group of malignant tumors arising from the soft tissue compartments, i.e smooth muscles, skeletal muscles, adipose tissue, blood vessels, connective tissue mesenchyme, neural tissue and other tumors of uncertain histogenesis(1). Soft tissue sarcomas are relatively rare tumors, represent less than 1% of adult malignancies based on data report from American Cancer Society (2). The crude incidence rate in Iraq for soft tissue sarcomas was 219/ 100,000 population during 2014 with male: female ratio of 1.3:1, and highest peak age between 30-34 years (3). The histological subtype and microscopic criteria are two parameters that influence the tumor grade which is the best predictor for aggressiveness. ( 2)Objectives:A retrospective evaluation of soft tissue sarcomas, using immunohistochemical study of Myosin, Desmin, Smooth muscle Actin (SMA) and Vimentin, aiming to re-evaluate the primary diagnosis and whether IHC assessment in soft tissue sarcoma is mandatory to reach a final interpretation.Material and Patients: A total of 50 cases soft tissue sarcomas were reviewed retrospectively from case archives of histopathology department/ Central Public Health Laboratory, for the period (2011-2018). The data for these cases were collected including the age, gender, site of the tumor and the preliminary biopsy report findings. Hematoxylin& Eosin (H&E) stain and IHC staining of unstained sections from formalin-fixed, paraffin-embedded tissue were performed using SMA, Vimentin, Desmin and Myosin.Methods: Age and gender distribution of the 50 cases was correlated. The IHC staining performed on 5 microns paraffin sections, applying peroxidase-Antiperoxidase technique and both positive and negative control slides were included for Smooth muscle actin (SMA), clone 1A4, Desmin (clone D33), Myosin (clone 2F12.A9) and Vimentin (Clone V9). The monoclonal antibodies used were from DAKO manufacturer as ready to use monoclonal antibodies while freeze-dried antibodies used for myosin with 1:20 dilution. Negative and positive control slides were used simultaneously. The staining intensity was assessed based on the percentage of positive cells expression of the four IHC monoclonal antibodies. Negative staining reported when no stain seen. Positive (+) means up to 30% of tumor cells with antigen expression. Positive (++) interpretation given when 31-60% of tumor cells show staining reaction, while Positive (+++) interpretation reported when over 60% of tumor cells showing staining reaction.Results:The staining interpretation of the four monoclonal antibodies were confirmatory for the original diagnosis in 40% of cases, while 60% of the final diagnoses were against the original interpretation. SMA was positive in 38/50 cases (76%). Desmin was positive in 8/50 cases (20%) Vimentin was positive in 42/50 of cases (84%), Myosin was positive in 30/50 of cases (71.4%).The current study focus on histological re-evaluation of different types of soft tissue sarcomas (including RMS-with its subtypes), MFH-storiform, pleomorphic and myxoid subtypes), fibrosarcoma, leiomyosarcoma, alveolar soft part sarcoma and synovial sarcoma depending on immunohistochemical study. The original diagnosis have been changed after the immunohistochemistry stain from fibrosarcoma to rhabdomyosarcoma and leiomyosarcoma , Malignant fibrous histiocytoma to rhabdomyosarcoma, alveolar rhabdomyosarcoma to Malignant fibrous histiocytoma, soft tissue sarcoma to rhabdomyosarcoma , pleomorphic MFH to pleomorphic rhabdomyosarcoma. Embryonal and alveolar rhabdomyosarcoma were confirmed by IHC as so. Leiomyosarcoma was confirmed as the same in one case. Embryonal Rhabdomyosarcoma changed to leiomyosarcoma by IHC positivity for desmin. Six cases of MFH were confirmed as malignant fibrous histiocytoma after IHC. Two cases of synovial sarcoma were re-evaluated as rhabdomyosarcoma. Vimentin revealed 100% positivity in 10 cases and regarded as a sensitive marker for mesenchymal tissue but it is not specific for certain types of sarcomas. The presence of desmin diffusely throughout a tumor is an indication of myoid differentiation and the presence of either SMA or desmin focally should not necessarily be equated with myoid lineage but rather with myofibroblastic lineage, which go in the same direction with Hirofumi N. et al. (1998).(4)Conclusions: The co-expression of SMA and Desmin helped in the diagnosis of leiomyosarcoma (LMS). Myosin expression was helpful in the diagnosis of rhabdomyosarcoma (RMS) and alveolar soft part sarcoma (ASPS). Smooth muscle actin (SMA) and vimentin were not specific for the diagnosis of malignant fibrous histiocytoma (MFH). High grade spindle cell sarcoma express SMA only without myosin or desmin can be categorized as pleomorphic myogenic sarcoma. By applying immunohistochemical markers, 60% of soft tissue sarcomas were different from the preliminary diagnosis while 40% of cases were supportive of the original H&E diagnosis.